Core Competencies for Pain Management: Results of an Interprofessional Consensus Summit - Fishman, Scott M (Blackwell Publishing Ltd, 2013)
OBJECTIVE: The objective of this project was to develop core competencies in pain assessment and management for prelicensure health professional education. Such core pain competencies common to all prelicensure health professionals have not been previously reported. METHODS: An interprofessional executive committee led a consensus-building process to develop the core competencies. An in-depth literature review was conducted followed by engagement of an interprofessional Competency Advisory Committee to critique competencies through an iterative process. A 2-day summit was held so that consensus could be reached. RESULTS: The consensus-derived competencies were categorized within four domains: multidimensional nature of pain, pain assessment and measurement, management of pain, and context of pain management. These domains address the fundamental concepts and complexity of pain; how pain is observed and assessed; collaborative approaches to treatment options; and application of competencies across the life span in the context of various settings, populations, and care team models. A set of values and guiding principles are embedded within each domain. CONCLUSIONS: These competencies can serve as a foundation for developing, defining, and revising curricula and as a resource for the creation of learning activities across health professions designed to advance care that effectively responds to pain.